Transmission EBSD (t-EBSD) to determine grain and grain boundary properties on nanostructured superconductor samples. (September 2019) - Koblischka-Veneva, A.; Koblischka, M. R.; Schmauch, J.; Murakami, M.
Abstract: The knowledge of the properties of the grains and their grain boundaries is essential for the further optimization of sample performance of various high- T c samples (YBa2 Cu3 O y (YBCO), Bi-based cuprates, MgB2, iron-based materials). In these materials either the grains are of nanometer dimensions or the various additions of secondary phase(s) to improve the flux pinning are required to be of nanometer dimensions, so a high achievable resolution and better imaging properties are important to obtain reasonably high image quality of the recorded Kikuchi patterns to enable automated orientation mapping using the EBSD technique. Therefore, the newly developed transmission-EBSD (t-EBSD) technique is the method of choice to analyze the grain and the grain boundary properties in such nanostructured superconducting materials. Several results obtained on MgB2, melt-textured, infiltration-growth processed YBCO and electrospun Bi2 Sr2 CaCu2 O8 nanowires are presented.